Institutionalization of pharmaceutical care in the municipality of Augusto Corrêa, Pará (Research, Society and Development, 2022)
Objective: To investigate the institutionalization of pharmaceutical care in the municipality of Augusto Corrêa, Pará. Method: Exploratory, retrospective, and descriptive research conducted in 2021. To obtain socioeconomic, demographic, epidemiological indicators, health services, total health expenditures, we used data from the Registry of Health Establishments of the Department of Informatics of the SUS, the Brazilian Institute of Geography and Statistics, the Institute of Applied Economic Research, and the Primary Care Information System. For information on governance practices, planning, management, technical-management and technical-assistance components of Pharmaceutical Assistance, structured forms were used, applied through the Survey Monkey® tool, via Internet®, to the coordination of Pharmaceutical Assistance of the Department Municipal Health in the municipality of Augusto Corrêa, Pará. Results: Augusto Corrêa has an Estimated Population of 46,937 inhabitants in 2021 and a Demographic Density of 37.10 population/km² in 2010. Territorial Area of ​​1,099,619 km² in 2020. It is part of the Amazon Biome, from the Northeast Mesoregion of Pará, Bragantina Microregion. 0.520 of Municipal Human Development Index in 2010. 0.4145 of Gini Index of Percapta Household Income in 2010. Does not fully comply with governance practices at the level of technical coordination of pharmaceutical assistance; in particular, personnel and competencies, principles and behaviors, organizational leadership, relationship with stakeholders, organizational strategy, trans-organizational alignment, governance structure, risk management and internal control, internal audit, accountability, and transparency. Also, I did not fulfill all the components for the Technical Management of Pharmaceutical Assistance and the Clinical Management of Medicines. Conclusion: It was found that the components of technical management of pharmaceutical care and clinical management of the drug were not fully complied with; as well as governance practices at the level of technical coordination of pharmaceutical assistance need to be improved; in particular, personnel and competencies, principles and behaviors, organizational leadership, relationship with stakeholders, organizational strategy, trans-organizational alignment, governance structure, risk management and internal control, internal audit, accountability and transparency.